Exploring the Role of Digital Tools in Vocabulary Acquisition: A Qualitative Study in the Context of English Education in Papua - Naing, Ince Rezky; Nemo, Maximus Leonardus; Rafra, Precilia (JURNAL PENA, 2025)
The use of digital learning tools has become increasingly influential in language education, particularly in facilitating vocabulary acquisition. However, in contexts such as Papua, Indonesia is characterized by limited resources and significant cultural diversity, the integration of these tools presents distinct challenges and opportunities. This study investigated the role of digital tools in enhancing vocabulary acquisition among English Education students in Papua, examined the challenges encountered by educators and learners, and proposes strategies for adapting these tools to better reflect the region's unique cultural and linguistic landscape. Adopting a qualitative research approach, the study gathered data through semi-structured interviews, classroom observations, and document analysis involving participants from both teachers and students of Papua. Thematic analysis was employed to extract key themes and patterns from the data. The findings indicated that digital tools, such as Kahoot, Quizziz, Quizlet and Duolingo, support vocabulary development by offering gamified, interactive, and self-directed learning opportunities. Nonetheless, their impact is constrained by infrastructural deficiencies, disparities in access to technology, and limited digital literacy among educators and students. Furthermore, the absence of culturally relevant content diminished engagement and reduced the tools’ effectiveness within the local context. The study concluded that while digital tools hold significant potential to enhance English Education, their successful implementation necessitates addressing infrastructural challenges, enhancing educator training, and developing culturally adapted resources. The research contributes to a deeper understanding of the complexities of digital learning in multilingual and under-resourced environments, offering actionable recommendations for improving language education in Papua.